Factors associated with time delay to carotid stenting in patients with a symptomatic carotid artery stenosis - Gröschel, Klaus (Springer-Verlag, 2011)
Treatment of a symptomatic stenosis is known to be most beneficial within 14 days after the presenting event but this can frequently not be achieved in daily practice. The aim of this study was the assessment of factors responsible for this time delay to treatment. A retrospective analysis of a prospective two-center CAS database was carried out to investigate the potential factors that influence a delayed CAS treatment. Of 374 patients with a symptomatic carotid stenosis, 59.1% were treated beyond ≥14 days. A retinal TIA event (OR = 3.59, 95% CI 1.47–8.74, p < 0.01) was found to be a predictor for a delayed treatment, whereas the year of the intervention (OR = 0.32, 95% CI 0.20–0.50, p < 0.01) and a contralateral carotid occlusion (OR = 0.42, 95% CI 0.21–0.86, p = 0.02) were predictive of an early treatment. Similarly, within the subgroup of patients with transient symptoms, the year of the intervention (OR = 0.28, 95% CI 0.14–0.59, p < 0.01) was associated with an early treatment, whereas a retinal TIA as the qualifying event (OR = 6.96, 95% CI 2.37–20.47, p < 0.01) was associated with a delayed treatment. Treatment delay was most pronounced in patients with an amaurosis fugax, whereas a contralateral carotid occlusion led to an early intervention. Although CAS is increasingly performed faster in the last years, there is still scope for an even more accelerated treatment strategy, which might prevent future recurrent strokes prior to treatment.